Los usos de la historia para construir proyectos de futuro: identidad, dinámicas territoriales y desarrollo en zonas rurales de Iberoamérica - Samper Kutschbach, Mario (2014)
This essay addresses the social use of historical knowledge for the design and implementation of long-term development strategies by social and institutional stakeholders in rural areas of Ibero-American countries. Applied historical knowledge in connection with area-based development refers to knowledge generated and/or applied in support of social management and participatory governance of predominantly rural areas. Its purpose is to understand the environmental, economic and technological, social, political/institutional and cultural dynamics, as a contribution to area-based development strategies in relation to a socially constructed project for the future. The area-based, systemic approach views rural areas as complex, multidimensional, dynamic and open systems, and their development as a participatory and endogenous social process set within the framework of public policies. Rural areas are social, cultural and historical constructs, and collective, area-based identities are crucial for their development. This essay refers specifically to the role of knowledge management, both regarding past history and present-day realities, in area-based development experiences in Spain, Brazil, Colombia, and Central America. It highlights the importance of an understanding of history as the study of societies over time, not only theirpast but also their present and future, to address core issues of development, in general, and area-based development, specifically.